GERAKAN MASYARAKAT PEDULI JANTUNG MELALUI EDUKASI GAYA HIDUP SEHAT UNTUK PENCEGAHAN PENYAKIT KARDIOVASKULAR DI KELURAHAN MOJOSONGO: Upaya meningkatkan kesadaran gaya hidup sehat di tingkat RT/RW - Bayu Akbar Khayudin; Sumardino; Sugiyarto (PPPM Stikes Banyuwangi, 2026)
Abstract: Cardiovascular disease is a leading cause of morbidity and mortality in Indonesia, largely driven by unhealthy lifestyles such as an unbalanced diet, lack of physical activity, and smoking. Promotive and preventive efforts through public education are crucial strategies for reducing the incidence of this disease. This community service activity aims to increase public knowledge and awareness about the importance of a healthy lifestyle in preventing cardiovascular disease in Mojosongo Village, RT 3 RW 5, Surakarta. Promoting health education, interactive discussions, and demonstrations of healthy lifestyle practices such as simple physical activity and healthy food choices. Evaluation used pre- and post-tests to measure improvements in participants' knowledge. The activity showed an increase in the good pre-test category of 30%, while at the post-test it increased by 58%, the sufficient category at the pre-test was 34%, while at the post-test was 24%, and the poor category at the pre-test was 36%, while at the post-test was 18%. This was significant in public knowledge about risk factors and the prevention of cardiovascular disease. Furthermore, participants showed high enthusiasm and commitment to implementing a healthy lifestyle in their daily lives. This activity demonstrates that community-based health education is effective in increasing public knowledge and awareness regarding cardiovascular disease prevention. The